Energy harvesting for autonomous thermal sensing using a linked E-shape multi-beam piezoelectric device in a low frequency rotational motion. (1st November 2019) - Ramírez, J.M.; Gatti, C.D.; Machado, S.P.; Febbo, M.
Highlights: A new-type shape of cantilever beam system for energy harvesting with ultra low frequency in rotational motion. A one-dimensional finite element is used to modeling the proposed energy harvester. The results are compared with experimental tests. The proposed harvester provides high energy for supplying to a thermal sensor LM335Z for 1.1 s every 38.58 s. Abstract: This paper presents a multi-beam energy harvester (MBT2ML) capable to convert kinetic energy from rotational motion at low frequency (<3 Hz) into usable electricity. The energy conversion is achieved by using a piezoelectric material MFC 8507 P2. The MBT2ML consists of two E-shape aluminum beams linked by a rigid steel beam. The multiple beams have attached masses made in steel at the free ends and a piezoelectric sheet MFC 8507-P2 bonded on one of the beams of the superior multi-beam trident. The MBT2ML is used to power an autonomous sensing system comprised by a storage device, a full bridge rectifier, a power conditioning circuit and a thermal sensor. The design of an energy harvester applied to monitoring the structural health of wind turbines of 30 kW is really a challenge from a physical viewpoint, due to drawbacks associated to extremely low operational frequencies (<3 Hz). For example, the output power is ruled by a cubic dependence on frequency and a linear dependence on mass, displacement and amplitude of excitation. The obtained data from the thermal sensor is transmitted to a notebook by a wireless data acquisition system (WDAS). The proposed harvester is a unique design which presents (i) low natural frequency into a compact size and (ii) the resonant frequency that closely matches the operating frequency to achieve maximum power generation. An experimentally validated nonlinear one-dimensional finite element formulation is used to investigate the effects of rotational motion on the electromechanical response of the harvester. The harvesting performance of the MBT2ML is assessed through varying the load resistance, the hub distances, the rotation speed (from 0 to 3 Hz), the position of the piezoelectric material and the electric connections (series and parallel) between two MFC 8507 P2 patches. The experimental results showed that the proposed harvester provides sufficient energy for supplying electric energy to a thermal sensor LM335Z during an active time of 1.01 s (delivering 200 readings) for each 38.53 s. This clearly indicates that our proposal of energy harvester provides sufficient electric power to a sensing system in a low frequency rotation scenario such as the one of wind turbines of 30 kW.